Pengaruh Penggunaan Bahasa Indonesia yang Komunikatif dalam Meningkatkan Efektivitas Informasi Kantor - Intan, Intan; Cahyati, Icha; Putri, Keysha Inka Kustiananda; Sujjada, Kholid Zaki; Muhammad, Maulana; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the influence of the use of communicative Indonesian in improving the effectiveness of communication in an increasingly modern and multicultural organizational environment. The method used is a literature study with a qualitative descriptive approach to analyze relevant literature on the strategic function of language in office management. Data collection is carried out through library studies, namely by examining various relevant written sources, such as scientific books, journal articles, research reports, and official language documents. The data analysis process is carried out in two main steps: data reduction and presentation. The results of this study indicate that the use of good and communicative Indonesian can strengthen professionalism, clarify messages and form a positive organizational culture. However, there are many challenges in the form of differences in the impact of foreign languages, digital culture, and intergenerational communication styles. This study highlights the importance of language training, organizational policies that support the use of standard languages, and the use of digital technology to maintain Indonesian. These findings confirm that Indonesian functions not only as a means of communication, but also as a means of managing information and symbolizing cultural identity in the organization.